Harmonisasi Prinsip Perdagangan Internasional pada GATT dalam Undang-Undang Nomor 7 Tahun 2014 tentang Perdagangan - Pangestu, Yudha; Sipahutar, Bernard; Ardianto, Budi (Faculty of Law, Universitas Jambi, 2021)
The purpose of this research is to find out how the implementation of the principles of international trade of General Agreement on Tariffs and Trade (GATT) and Law Number 7 of 2014 concerning Trade and to find out how the harmonization of the principles of international trade of General Agreement on Tariffs and Trade (GATT) in Law No. 7 of 2014 concerning Trade. This type of research is normative legal research. The results of the research that have been carried out are the implementation of the principles of international trade of General Agreement on Tariffs and Trade (GATT ) and Law Number 7 of 2014 concerning Trade, based on Law Number 7 of 1994 concerning Ratification of the Agreement Establishing The World Trade Organization. World Trade) contains content or material that contains GATT / WTO principle arrangements, namely in letters A, B, and C, as well as harmonization of the principles of international trade of General Agreement on Tariffs and Trade (GATT) in Law Number 7 of 2014 concerning Trade, that In Law Number 7 of 2014 concerning Trade, there are several legal principles in international trade arrangements. The conclusion of this study is that based on Law Number 7 of 1994 concerning Ratification of the Agreement Establishing The World Trade Organization, there is content or material that contains the principles of GATT / WTO, namely in letters A, B, and C, as well as harmonization of the principles of international trade of General Agreement on Tariffs and Trade (GATT) in Law Number 7 of 2014 concerning Trade, that in Law Number 7 of 2014 concerning Trade there are several legal principles in regulating international trade. Â